Domestic Role Of Husband During Pregnancy Wife - Agustin Dwi Syalfina; Nurun Ayati Khasanah; Wiwit Sulistyawati; Dian Irawati; Sari Priyanti (Universitas STRADA Indonesia, 2020)
The understanding of positive gender equality in society has many benefits in life, especially in reducing cases of gender injustices, household problems and improving maternal health, especially in pregnancy. Husbands should be willing to spend some time to take care of employees work in addition to earning a living. Support husband in participating in the role of domestic important in preventing complications during pregnancy until after childbirth. The purpose of this research is to analyze factors that are influenced by the role of domestic husband. The research method used is quantitative with Cross sectional design. Data is obtained by conducting interviews on husbands who accompany expectant pregnancy with a questionnaire guide. The factor affecting husband's participation in household work is knowledge and desolation about gender. Education to the public about gender equality is seen from a much needed role to reduce incomprehension and misrepresentation of society on Gender Equality